Adsorption of small organic molecules on graphene - Lazar, Petr; Karlický, František; Jurečka, Petr; Kocman, Mikuláš; Otyepková, Eva; Šafářová, Klára; Otyepka, Michal (Journal of the American Chemical Society, 2013)
We present a combined experimental and theoretical quantification of the adsorption enthalpies of seven organic molecules (acetone, acetonitrile, dichloromethane, ethanol, ethyl acetate, hexane, and toluene) on graphene. Adsorption enthalpies were measured by inverse gas chromatography and ranged from -5.9 kcal/mol for dichloromethane to -13.5 kcal/mol for toluene. The strength of interaction between graphene and the organic molecules was estimated by density functional theory (PBE, B97D, M06-2X, and optB88-vdW), wave function theory (MP2, SCS(MI)-MP2, MP2.5, MP2.X, and CCSD(T)), and empirical calculations (OPLS-AA) using two graphene models: coronene and infinite graphene. Symmetry-adapted perturbation theory calculations indicated that the interactions were governed by London dispersive forces (amounting to ∼60% of attractive interactions), even for the polar molecules. The results also showed that the adsorption enthalpies were largely controlled by the interaction energy. Adsorption enthalpies obtained from ab initio molecular dynamics employing non-local optB88-vdW functional were in excellent agreement with the experimental data, indicating that the functional can cover physical phenomena behind adsorption of organic molecules on graphene sufficiently well.
Keywords: molekulární modely; Graphite; Chromatography, Gas; grafit; termodynamika; chromatografie plynová; Models, Molecular; Static Electricity; Adsorption; organické látky; chemické modely; mikroskopie elektronová rastrovací; Microscopy, Electron, Scanning; statická elektřina; Models, Chemical; Thermodynamics; Organic Chemicals; adsorpce